MDCT in suspected lumbar spine fracture: comparison of standard and reduced dose settings using iterative reconstruction. Issue 7 (July 2018) - Weinrich, J.M.; Well, L.; Regier, M.; Behzadi, C.; Sehner, S.; Adam, G.; Laqmani, A.
Abstract : Aim: To compare standard (SD-) and reduced-dose computed tomography (RD-CT) in combination with iterative reconstruction (IR) in emergency patients with suspected lumbar spine fracture. Material and methods: Forty emergency patients with suspected lumbar spinal disorder who underwent RD-CT and 40 body mass index-matched patients undergoing SD-CT were enrolled in this retrospective study. Raw data for RD-CT were reconstructed using two increasing IR levels (IRL) 4 and 6, while SD-CT was reconstructed with IRL3. Two radiologists assessed image quality, image noise, and reader confidence in interpreting findings of spinal fractures in a blinded manner. Results: Effective radiation dose was reduced by 50% using RD-CT. Overall subjective image quality (SIQ) was high for both protocols and slightly superior in the RD-CT protocol for both IRL compared to SD-CT. The detection rate of spinal disorders was high for both protocols with a high interobserver agreement. Conclusion: RD-CT with higher levels of IR results in substantial dose reduction of 50% in lumbar spine CT while maintaining an excellent subjective image quality resulting in a high diagnostic confidence. Highlights: High tube voltage along with low reference mAs allows 50% dose reduction. IR allows reduced-dose spine CT with high image quality. Readers confidence for interpretation reduced-dose CT of the lumbar spine is high.